SPECIFIC IDENTIFICATION OF VIBRIO PARAHAEMOLYTICUS EMPLOYING MONOCLONAL ANTIBODY BASED IMMUNOASSAY - RAKSHA AJITPRASAD MANIYANKODE; JOSEPH JEYABALAJI KINGSTON; HARISHCHANDRA SRIPATHY MURALI; HARSH VARDHAN BATRA (International Journal of Pharma and Bio Sciences, 2013)
The present study was carried out to achieve a simple, specific and cost effective detection system for Vibrio parahaemolyticus. The Outer Membrane Proteins (OMPs) of V. parahaemolyticus were extracted by treating the cell pellet with N- lauroyl sarkosyl and analysed by SDS-PAGE. Female BALB/c mice were immunized with the crude OMP extract and antigenicity was confirmed by subsequent Western blotting with anti-OMP antisera. The mice with higher antibody titre were selected as spleen donors for fusion. OMP based indirect plate and dot ELISA were standardized for screening of hybridoma and four hybridoma cell lines producing monoclonal antibodies (MAbs) were stabilized. Among these, MAb 212 detected a 36 kDa OMP that was present in all V. parahaemolyticus strains irrespective of their serotypes. Cross-reactivity of this MAb was observed only with V. alginolyticus and Aeromonas spp. from different organisms tested, but these species could also be clearly differentiated from each other in Western blot as V. alginolyticus had reaction at 38 kDa and Aeromonas sp. reacted at 39 kDa protein. These species therefore, appear to share the same MAb 212 epitope located at different antigens. These specific and sensitive assays could detect diverse V. parahaemolyticus serovars and may be applicable as a reliable and rapid diagnostic procedure for the identification and direct detection of V. parahaemolyticus in seafood samples.